ANALYSIS THE FACTORS OF EMPLOYEE RESISTANCE ON ORGANIZATIONAL CHANGE AT LOTUS RESORT MOKUPA NORTH SULAWESI - Moonik, Hanri Hendi; Saerang, David P. E.; Rumokoy, Farlane s. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Abstract: In an organization, a change is needed. An organization capable of facing change can be referred to as a developing organization. One of the obstacles in the organization is resistance to change. Resistance in an organization has a negative impact on running the changes, because with resistance attitudes, a person will reject changes and will not experience changes or progress in the organization. In this research, there are 20 variables that defined as factors that influence employee resistance at Lotus Resort. The analysis and discussion from this research there are 13 variables that correlated with the factor that already conducted. The findings from the factoring process there are 3 factors that influence employee resistance at Lotus Resort. First factor is Trust In Management with 9 independent variables (Fear Of Loss Of Job, Uncertainty, Leadership Style, Regulations By Government, Trust In Management, Rumors, Structural Inertia, Decision Making Process and Self Development). Second factor is The Ability Of The Change Agent with 4 independent variables (Time, Ability Of The Change Agent, Organizational Structure and Relationship With The Colleagues). Third factor is Poor Communication with 2 independent variables (Poor Communication and Capability Of Employees). Where the research shows that Trust In Management, Ability Of The Change Agent and Poor Communication are contributing factor in affecting the resistance.Â Keywords: Employee Resistance, Organizational Change, Confirmatory Factor Analysis.